Evaluation of vascular tissue disorders and regional bleeding under chronic reduced preparative atphosis - N.N. Khabibova (Proceedings of The ICECRS, 2019)
At present, the biochemical and morphological phases of the development of inflammation in the area of tissue damage are distinguished, in particular, the rate of formation of vasoactive and chemotactic substances that determine the stereotypical nature of local vascular and tissue changes (1,4,5,6). Concerning the dynamics of the release of inflammatory mediators in the alteration zone, the initiating role of histamine should be noted.